Nation and empire as two trends of political organization in the Iron Age Levant - Mei, Hualong (Culture and history of the ancient Near East, 2024)
"In Nation and Empire as Two Trends of Political Organization in the Iron Age Levant MEI Hualong offers an analysis of national and imperial ideologies--two political principles that influenced the establishment, consolidation and expansion of trans-local/trans-tribal polities in the Iron Age Levant. By examining key terminologies, historical accounts and literary sources, MEI argues that the elites of ancient nations may attempt to reshape their political and cultural identity in imperial terms (vice versa, but to a lesser extent). The conceptual transformation from the one to the other is closely related to the political entity's consciousness and understanding of limits and boundaries: political and cultural, real and imagined"--